(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study aims to investigate the most important factors for hiring decision from employer’s perspective in Commercial Banks. Methods: Data collection of employers’ a simple random sampling technique, targeting 135 employers of commercial banks. The study utilized a self-administered questionnaire featuring a rigorous seven-point Likert scale. Analysis of research data was done using smart PLS 4 version and SPSS software. Results: The findings revealed that percentage of marks and Internship Experiences are the major factors. The obtained results are very useful to identify the preferences or priorities given by the employers, which could be referred by the prospective job applicants in professional workplace. Conclusion: from the result of research conducted, it can be concluded that if academic institution grooms their students considering the factor then there is a higher possibility that good number of students can be hired in commercial bank.